2021
DOI: 10.1037/ort0000536
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ACES assessment within a collaborative practice model: Implications for health equity.

Abstract: It is now well understood that exposure to Adverse Childhood Experiences (ACEs) is negatively linked to health and well-being across the lifespan. In an effort to disrupt ACEs exposure and its effects, there is a nationwide movement to screen for ACEs in primary care, despite a lack of wellestablished guidelines for assessing and responding to risk within routine care. Additionally, developing culturally responsive models of ACEs assessment is imperative, particularly because racial and ethnic minority populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(86 reference statements)
0
7
0
Order By: Relevance
“… 41 For most studies using the ACE questionnaire, a score of ≥4 ACE was used to indicate high ACE exposure. Of the studies that did not use a version of the ACE questionnaire, 2 used the Post-Traumatic Stress Disorder section of the Schedule for Affective Disorder and Schizophrenia for School-Age Children Present and Lifetime (to assess for domestic violence and exposure to sexual and/or physical abuse) and the European Addiction Severity Index (to assess parental employment status) 44 45 ; 2 used the interRAI Child and Youth Mental Health Assessment; 1 used an adapted version of the Traumatic Event’s Screening Inventory 40 ; 1 used the Center for Youth Wellness ACE Questionnaire (17-item child and 19-item teen) 49 ; 1 used the Traumatic History Profile 8 ; 1 developed and used the Whole Child Assessment which included ACE questions 50 ; and 1 employed seven measures including the Childhood Trauma Questionnaire-Short Form, Trauma Experiences Checklist, Parental Nurturance Scale, Parental Harsh Discipline Scale, Violence Exposure Scale, Friends’ Delinquent Behavior Scale and School Connectedness Scale. 52 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 41 For most studies using the ACE questionnaire, a score of ≥4 ACE was used to indicate high ACE exposure. Of the studies that did not use a version of the ACE questionnaire, 2 used the Post-Traumatic Stress Disorder section of the Schedule for Affective Disorder and Schizophrenia for School-Age Children Present and Lifetime (to assess for domestic violence and exposure to sexual and/or physical abuse) and the European Addiction Severity Index (to assess parental employment status) 44 45 ; 2 used the interRAI Child and Youth Mental Health Assessment; 1 used an adapted version of the Traumatic Event’s Screening Inventory 40 ; 1 used the Center for Youth Wellness ACE Questionnaire (17-item child and 19-item teen) 49 ; 1 used the Traumatic History Profile 8 ; 1 developed and used the Whole Child Assessment which included ACE questions 50 ; and 1 employed seven measures including the Childhood Trauma Questionnaire-Short Form, Trauma Experiences Checklist, Parental Nurturance Scale, Parental Harsh Discipline Scale, Violence Exposure Scale, Friends’ Delinquent Behavior Scale and School Connectedness Scale. 52 …”
Section: Resultsmentioning
confidence: 99%
“…One study used the ACE 10-item questionnaire (completed by parents of infants; n=151, infant M age=5.77 months, SD=1.98, 49.7% male) while the other used the ACE 17-item (completed by parents of children; n=114, child M age=8.4 years, SD=2.5, 57% male) and 19-item questionnaires (completed by adolescents; n=49, M age=14.7 years, SD=1.3, 40.8% male). Both studies found administering the ACE questionnaire to be highly feasible with 92% 47 and 97% 49 of potential participants completing the questionnaire. Given the small number of studies looking at the administration of ACE in health settings and that both studies were undertaken in the USA, further research is indicated for generalisability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations